2018
DOI: 10.3991/ijet.v13i03.7712
|View full text |Cite
|
Sign up to set email alerts
|

Using Google to Search Language Patterns in Web-Corpus: EFL Writing Pedagogy

Abstract: Abstract-The use of the Web as a corpus of language data and Google as a concordancer has been considered as one of the promising directions in the development of the EFL pedagogy. It has been stated by several researchers that the use of the popular search engine Google to search and define authentic language patterns is mostly advantageous for teaching EFL writing as well as mastering learner autonomy of the EFL students. The present article focuses on the advantages and opportunities of Google as a search e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…online dictionary in by a postgraduate EFL student in academic writing tasks, it was revealed that all corpus resources used contributed to proofreading and editing and increased the learner's linguistic awareness (Kotamjani et al, 2017). Studies also underscore that with adequate training GS can enhance naturalness of learner writing (Acar et al, 2011;Geluso, 2013;Shei, 2008) and improve error correction (Geiller, 2014;Kvashnina & Sumtsova, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…online dictionary in by a postgraduate EFL student in academic writing tasks, it was revealed that all corpus resources used contributed to proofreading and editing and increased the learner's linguistic awareness (Kotamjani et al, 2017). Studies also underscore that with adequate training GS can enhance naturalness of learner writing (Acar et al, 2011;Geluso, 2013;Shei, 2008) and improve error correction (Geiller, 2014;Kvashnina & Sumtsova, 2018).…”
Section: Introductionmentioning
confidence: 99%